Muakhi culture as ethnic conflict management in Lampung - Luthfi Salim; Idrus Ruslan (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
The transmigration program forms Lampung society to be multicultural that easily triggers the emergence of ethnic conflicts. In Lampung, it has unexpectedly formed enclaves that cause migrants and local people to not be integrated so that there is polarization and an economic gap between migrants and local people. This is because the economy of migrants advances which causes social jealousy. This study aimed to explain muakhi as conflict management from pre-conflict to post-conflict. This study was qualitative research with phenomenology and multiple case approaches. The research data were obtained by in-depth interviews. The results of this study are first, muakhi in pre-conflict management is managed by the traditional leaders to conduct deliberation and agreement. Second, muakhi in post-conflict management is managed and controlled by all elements of the community. The village officers, traditional leaders, religious leaders, community leaders, or mass organizations remind each other by means of cooperation with the conflicting parties. This study concluded that muakhi is able to create social and media integration and a forum for creating peace in accordance with the values and norms in the lives of the community.